How to solve this first order linear differential equation?

#xy'-1/(x+1)y=x #
y(1) = 0

(According to our professor, I.F. = #e^(intf(x))#, and we should just leave the integral be for now if the integral cannot be solved by hand or conventional methods)

Answer 1

# y = x/(x+1)(x + lnx -1) #

We have:

# xy'-1/(x+1)y=x # with # y(1) = 0#

We can use an integrating factor when we have a First Order Linear non-homogeneous Ordinary Differential Equation of the form;

# dy/dx + P(x)y=Q(x) #

So, we can put the equation in standard form:

# y'-1/(x(x+1))y = 1 #

Then the integrating factor is given by;

# I = e^(int P(x) dx) # # \ \ = exp(int \ -1/(x(x+1)) \ dx) #

We can readly evaluate this integral if we perform a partial fraction decomposition of the integrand:

# 1/(x(x+1)) -= A/x + B/(x+1) => 1 -= A(x+1)+Bx #

Then:

# x= \ \ \ \ \ 0 => A=1 # # x=-1 => B=-1#

So we can write:

# I = exp(int \ -1/x + 1/(x+1) ) \ dx) # # \ \ = exp(ln(x+1)-lnx) # # \ \ = exp( ln((x+1)/x) ) # # \ \ = (x+1)/x #
And if we multiply the DE [A] by this Integrating Factor, #I#, we will have a perfect product differential (in fact the original equation);
# :. ((x+1)/x)y' - ((x+1)/x) 1/(x(x+1))y = ((x+1)/x) #
# :. (1+1/x)y' - 1/x^2y = 1+1/x #
# :. d/dx ((1+1/x)y) = 1+1/x #

This is now separable, so by "separating the variables" we get:

# (1+1/x)y = int \ 1+1/x \ dx #

Which is trivial to integrate to get the General Solution:

# (1+1/x)y = x + lnx + C #
Applying the initial condition #y(1)=0# we get:
# 0 = 1 +ln1 + C => C=-1 #

Leading to the Particular Solution:

# (x+1)/x \ y = x + lnx -1 #
# :. y = x/(x+1)(x + lnx -1) #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

#y=x/(x+1)(x+lnx-1)#

.

#xy'-1/(x+1)y=x#

A first Order linear Differential Equation has the form of:

#y'(x)+p(x)y=q(x)#
Let's put our ODE in this form by dividing the entire equation by #x#:
#y'-1/(x(x+1))y=1#, which shows that:
#p(x)=-1/(x(x+1))# and #q(x)=1#

The integration factor is:

#mu(x)=e^(intp(x)dx)=e^(int-1/(x(x+1))dx)=e^I#
#I=int-1/(x(x+1))dx=-int1/(x(x+1))dx#

We can use partial fraction expansion to solve it:

#1/(x(x+1))=A/x+B/(x+1)=(A(x+1)+Bx)/(x(x+1))=(Ax+A+Bx)/(x(x+1))=((A+B)x+A)/(x(x+1))#
#A+B=0# and #A=1#
Therefore, #B=-1#
#I=-int(1/x-1/(x+1))dx=-lnabsx+lnabs(x+1)+C#
#mu(x)=e^(-lnabsx+ln(x+1)+C)=e^-lnabsx*e^(lnabs(x+1))*e^C=1/e^lnabsx(e^lnabs(x+1))e^C=1/x(x+1)e^C=(e^C(x+1))/x#
The constant #e^C# is redundant and can be ignored. Therefore,our integration factor is:
#mu(x)=(x+1)/x#

Now, we multiply both sides of our ODE by this integration factor:

#y'((x+1)/x)-1/(x(x+1))((x+1)/x)y=(x+1)/x#

Then, we simplify and refine:

#((x+1)y')/x-y/x^2=1/x+1# #color(red)(Equation-1)#
If #f=(x+1)/x and g=y# then applying the product rule of differentiation we get:
#(f*g)'=f*g'+f'*g#
#f'=(x-(x+1))/x^2=-1/x^2# (we used the quotient rule)
#g'=y'#
#f*g'+f'*g=((x+1)/x)y'+(-1/x^2)y=((x+1)y')/x-y/x^2#
which is the same as Left Hand Side of #color(red)(Equation-1)#.
Therefore, the Right Hand Side of it must be equal to #(f*g)'#.
#(f*g)'=1/x+1#
#(((x+1)y)/x)'=1/x+1#, i.e:
#d/dx((x+1)/xy)=1/x+1#

We now take the integral of both sides:

#(x+1)/xy=int(1/x+1)dx=int1/xdx+intdx#
#(x+1)/xy=lnx+x+c#
We now proceed to isolate #y#:
Let's multiply both sides by #x#:
#(x+1)y=xlnx+x^2+cx#
Let's divide both sides by #x+1#:
#y=(xlnx+x^2+cx)/(x+1)#

Now, we can apply the initial conditions:

#y(1)=0#
#((1)(ln1)+(1)^2+c(1))/((1)+1)=((1)(0)+1+c)/2=(c+1)/2=0#
#c+1=0#
#c=-1#

Therefore,

#y=(xlnx+x^2-x)/(x+1)=x/(x+1)(x+lnx-1)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To solve a first-order linear differential equation, follow these steps:

  1. Write the equation in the standard form: ( \frac{dy}{dx} + P(x)y = Q(x) ).

  2. Identify the integrating factor, denoted by ( \mu(x) ), which is given by ( \mu(x) = e^{\int P(x) , dx} ).

  3. Multiply both sides of the equation by the integrating factor: ( \mu(x) \left(\frac{dy}{dx} + P(x)y \right) = \mu(x) Q(x) ).

  4. Simplify the left-hand side to get ( \frac{d}{dx} (\mu(x) y) ).

  5. Integrate both sides with respect to ( x ): ( \int \frac{d}{dx} (\mu(x) y) , dx = \int \mu(x) Q(x) , dx ).

  6. Solve the resulting equation for ( y ) by integrating both sides.

  7. If necessary, solve for any constants of integration using initial conditions or boundary conditions.

This method allows you to solve first-order linear differential equations efficiently.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7